The high er education Institutions’ enviromental engagement in Colombia - Callejas-Restrepo, María Mercedes; Sáenz-Zapata, Orlando; Plata-Rangel, Ángela María; Holguín-Aguirre, María Teresa; Mora-Penagos, William Manuel (Universidad Pedagógica y Tecnológica de Colombia, 2018)
The aim of this article is to present an updated overview of the progress achieved by Higher Education Institutions (HEIs) in Colombia in the institutionalization of the environmental engagement. The document explores the incorporation of environmental issues into domains including, in addition to the fundamental activities—teaching, research, and extension—institutional policies and participation, and environmental planning and management. A survey was conducted with 60 private and public HEIs located in different regions of the country. This is a qualitative exploratory research supported by analysis of descriptive statistics. It was carried out based on a scale fixed for each domain, which uses percentages as a basis for indicating the levels of environmental engagement of each of the HEIs. Governance and participation constituted the highest-performing domain, showing the interest of the HEIs in strengthening environmental policies. Campus management and planning was the less-performing domain. These results establish the need to generate self-regulation and institutional improvement strategies, and to promote processes for further research.